Carpal Tunnel Syndrome: A New Adverse Effect of Immune Checkpoint Inhibitors, 11 Cases. Issue 3 (16th April 2021) - Lechevalier, Diane; Denis, Daphné; Le Corre, Yannick; Heidelberger, Valentine; Brunet-Possenti, Florence; Longvert, Christine; Piot, Jean M.; Maillard, Hervé; Beneton, Nathalie
Abstract : This study aims at reporting 11 cases of carpal tunnel syndrome (CTS) occurring in patients on immunotherapy. The increasing use of immune checkpoint inhibitors in oncodermatology is associated with the appearance of immunologic adverse effects linked to nonspecific stimulation of the immune system. CTS has not been reported in this context. A retrospective multicenter review was performed on CTSs occurring on immunotherapy and confirmed with electroneuromyography. Data were collated from patients' files. Most of the time, CTS was severe, bilateral, with a motor deficit and confirmed axonal damage on electroneuromyography. In 4 cases, it was associated with rheumatological adverse effects (arthralgia/inflammatory synovitis). The most effective treatment appeared to be general corticosteroid therapy, even at low doses (<15 mg/d), or surgery. An imputability of the CTS of these patients to immunotherapy was considered due to the unusual intensity of the symptoms and the absence of other predisposing factors (diabetes and dysthyroidism well-controlled). Its combination with other immunologic adverse effects and the efficacy of general corticosteroid therapy suggests an immunologic origin. CTS is probably an immunologic adverse effect of immunotherapy. It is often severe or misleading in presentation and affects quality of life. The recognition of this adverse effect should make it possible to provide patients with appropriate care.